Exploring the process of family interventions for psychosis in relation to attachment, attributions and problem‐maintaining cycles: an IPA study. Issue 4 (23rd July 2015) - Rapsey, Estelle H. S.; Burbach, Frank R.; Reibstein, Janet
Abstract : This study sought to understand how the experience of family interventions (FI) for psychosis helped family members to develop their thinking about their attachment experiences and the attributions made about a relative, and how these discussions helped to inform their understanding about problem‐maintaining cycles, that is, the interactional way in which difficulties could be maintained. Ten individuals who had attended an FI service participated in a semi‐structured interview. The transcript analysis used interpretative phenomenological analysis. The analysis yielded four themes: a supportive therapeutic relationship and safe therapeutic space; understanding patterns of relating and identifying when family interactions become unhelpful; making sense of psychosis and developing a sense of agency. The FI was experienced as helpful in bringing about changes in the way family members construed each other and psychosis, and this influenced patterns of relating. Practitioner points: A safe therapeutic space for both client and family can help them discuss sensitive issues, restore emotional connections and reach better understandings of psychosis. Exploring family relational experiences, attachment and attributions can be helpful in gaining understanding of how problems in psychosis are maintained. Family intervention can help families identify helpful versus unhelpful interactions and make positive changes.